Estudio de factibilidad para la creación de lava autos en el distrito de Buenaventura (2013)
The structure and development of this research is based on the study of the behavior of the service sector in the district of Buenaventura, in order to get to know prospects and customers satisfaction in terms of car washes in the are currently located in the district of Buenaventura. The main objective of this research is to analyze the existing market to achieve bonaerense dabble with a car wash with high-tech machinery and trained staff to provide the service to potential customers. Therefore, we know the market study and the behavior of the service sector in the district for the period 2012 Buenaventura.